Analisis Perilaku Generasi Millenials terhadap Permintaan Transportasi Online di Kota Semarang - Afidatun Nisa (Diponegoro Journal of Economics, 2020)
This study aims to examine the behavior of millennial generation towards online transportation demand in the city of Semarang. Semarang is one of the metropolitan cities in Indonesia with 43.27% of the population being millennial generation in 2018. Current technological developments have changed the conventional transportation system to online with a real-time ridesharing system. This system has changed the pattern of transportation demand in the community. This study uses primary data with questionnaire techniques. The number of samples in this study were 100 taken by proportionate stratified random sampling methods. Furthermore, this study uses multiple linear regression methods with cross-section data, with the dependent variable is the intensity of the use of online transportation. As seven independent variables used in the estimation are the cost of travel, income, peer-group, transport anxiety, perceived usefulness, quality, and private mode ownership. The results showed that the cost of travel had a negative and significant effect on the intensity of online transportation use. Income, perceived usefulness, and quality have a positive and significant effect on the intensity of online transportation use. Meanwhile, peer-group and trnasport anxiety have a positive and insignificant effect on the intensity of the use of online transportation by millennials in the city of Semarang.